Implementasi Algoritma Camellia Dalam Penyandian Pesan SMS Pada Telepon Seluler - Halimah Ani; Surya Darma Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
SMS technology also does not guarantee the security and confidentiality of messages sent. The distribution of message content is very vulnerable to interference or theft by irresponsible parties, because the message content that is plaintext (text-light) can be read by anyone, to reduce the risk caused by one way of overcoming it is to implement a cryptographic algorithm on the message sent. The cryptographic algorithm used is the Camellia cryptographic algorithm with a 128-bit key length. Camellia is a block cipher designed by experts in research and development in cryptographic techniques. With the encrypted message sent then someone who managed to steal information about the SMS message sent, then someone who succeeded in stealing information from the text message sent would find it difficult to know the contents of the message. Designed and built an application program using Android with an Android system of at least version 2.2 to facilitate users in encoding SMS messages.